Kontrol' i charakteristika vzaimosvjazi funkcional'noj i techniceskoj podgotovlennosti v ženskom legkoatleticeskom mnogobor'e - Ogandžanov, A. L.; Tjagacev, A. A. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2020)
The article contains the research of the generation of a methodology for monitoring the technical readiness of all-rounder sportswomen at the stage of higher sportsmanship. The research contains the determination of morphological indicators of all-rounder sportswomen in the competitive period. It is proposed to carry out further individual correction of training of sportswomen on this objective basis.